Linoleic acid content in adipose tissue and coronary heart disease. Issue 6533 (31st May 1986) - Riemersma, R A; Wood, D A; Butler, S; Elton, R A; Oliver, M; Salo, M; Nikkari, T; Vartiainen, E; Puska, P; Gey, F
Abstract : The possibility of an inverse relation between essential fatty acids in adipose tissue, in particular linoleic acid, and mortality from coronary heart disease was studied by a cross sectional survey of random population samples of apparently healthy men aged 40-49 from four European regions with differing mortality from coronary heart disease. The proportion of linoleic acid in adipose tissue was lowest in men from north Karelia, Finland, where mortality from coronary heart disease is highest, and highest in men from Italy, where mortality is lowest, with intermediate proportions in men from Scotland and south west Finland. Similar gradients were observed for the desaturation and elongation products dihomo-gamma-linolenic and arachidonic acid. The proportion of saturated fatty acids in adipose tissue was highest in Finland, intermediate in Scotland, and lowest in Italy. Italian men also had the highest proportion of oleate in their adipose tissue and the lowest proportion of myristoleate and palmitoleate. Finnish men were more obese and had a higher blood pressure. Serum cholesterol concentration was higher in north Karelia and south west Finland than in Scotland or Italy. High density lipoprotein (HDL) cholesterol concentrations reflected the regional differences in serum cholesterol, being higher in Finland and lower in Italy. The ratios of HDL cholesterol to total cholesterol, however, did not differ. The regional differences in linoleic acid in adipose tissue remained highly significant when the observed differences in other known risk factors for coronary heart disease among the four areas were taken into account by multivariate analysis. The gradients in proportions of polyunsaturated fatty acids probably reflect differences in dietary intake of linoleic acid.